Understanding endometriosis underfunding and its detrimental impact on awareness and research - Ulrik Bak Kirk; Anne Sofie Bank-Mikkelsen; Dorte Rytter; Dorthe Hartwell; Henrik Marschall; Mette Nyegaard; Mikkel Seyer-Hansen; Karina Ejgaard Hansen (npj Women's Health, 2024)
Endometriosis affects approximately 190 million women globally. Many individuals with endometriosis face complex journeys through the healthcare system, set against a backdrop of historically underfunded research into women’s health. This study investigates the funding allocated to endometriosis up to 2023 by analysing the top 100 granting foundations in Denmark and comparing it to diabetes and inflammatory bowel disease, with similar prevalence and impact. We found that endometriosis remains significantly underfunded.